Sudden cardiac death and antipsychotic medications: literature review - V. P. Volkov (Кардиоваскулярная терапия и профилактика)
The review summarises the evidence from international publications on sudden cardiac death (SCD) in psychiatric patients receiving neuroleptics. Modern SCD definitions are presented, together with the relevant epidemiological data. The pathogenesis of fatal cardiac arrhythmias, caused by cardiotoxic effects of antipsychotic medications, is discussed. Electrocardiographic changes, in particular QT interval changes, as well as risk factors of SCD and main principles of its prevention, are described in detail.